CHINA IMPULSIVE PURCHASING BEHAVIOUR AND HEDONIC MOTIVATION: THE IMPACT OF ELECTRONIC WORD OF MOUTH - Ooi Kok Loang; Liu Shukun (International Journal of Accounting, Finance and Business, 2024)
This study investigates the impact of electronic word of mouth (eWOM), user-generated content (UGC), and social media engagement on impulsive purchasing behavior within the context of the Chinese e-commerce market. As digital interactions increasingly shape consumer decision-making processes, this research aims to elucidate the complex relationships between these digital variables and impulsive buying tendencies, with a particular focus on the moderating role of hedonic motivation. Drawing on the Theory of Planned Behaviour (TPB), this study examines how attitudes, subjective norms, and perceived behavioral control influence consumer trust and subsequent impulsive purchasing decisions. Utilizing a quantitative methodology, data were collected through structured questionnaires, and the analysis was conducted using SPSS and SMARTPLS 4.0. The findings reveal significant insights into the mechanisms through which eWOM, UGC, and social media engagement drive impulsive purchases, offering valuable implications for businesses seeking to optimize their digital marketing strategies in the competitive Chinese market.